ANALISIS PROKSIMAT DAN NILAI KALOR BRIKET HIBRID (BROWN COAL – SEKAM PADI) DENGAN PEREKAT LIQUID VOLATILE MATTER (LVM) YANG DIPREPARASI DENGAN METODE PIROLISIS - Rahmat .; H.M. Jahiding; E.S. Hasan (Jurnal Aplikasi Fisika, 2015)
Research on quality testing of briquettes hybrid (lignite - rice husk) using proximate analysis, calorific value and flame test. The purpose of this study was to determine the characteristics of proximate, calorific value and flame test using pyrolysis method, with adhesive Liquid Volatile Matter (LVM) the results of pyrolysis of rice husk. Lignite is heated in an oven with a temperature of 105 ° C and in the pyrolysis of rice husk with a variation of temperatures of 400 ° C, 500 ° C to 600 ° C and 700 ° C. Hybrid powder briquettes (coal blend of young and rice husk) made using Liquid Volatile Matter (LVM) as the glue that varied with the composition of 5% to 10% and 15% of the total sample period. Young coal and grain size of 100 mesh rice husks. Samples were molded by using a mold cylinder with a diameter of 1.92 cm with no restriction compacting of briquettes. Briquettes hybrid quality testing include determination of the parameters: water content, substance evaporates, ash content, bound carbon and calorific value. Quality testing and lignite briquettes hybrid rice husk covering sulut time and burning time. The results showed that the increase in the pyrolysis temperature can lower water content and volatile matter content and ash content and tends to increase carbon dependent. Briquettes optimum hybrid has a calorific value of 6255 cal / g at the pyrolysis temperature of 400 ° C adhesive 5%. Temperature increases are likely to affect the time sulut and briquettes burning time hybrid, where the higher the temperature, the higher the time is getting short time sulut and flames.